PENYELESAIAN SISTEM PERSAMAAN INTEGRAL VOLTERRA DENGAN METODA DEKOMPOSISI ADOMIAN - Okmi Zerlan; M. Natsir; Endang Lily (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the construction of the systems of Volterra integral equations from extended Lane-Emden equation. The system of Volterra integral equations of the settlement is determined by using the Adomian Decomposition Method. The Adomian decomposition method gives reliable result for analytic approximate solutions of these systems. The results are supported by investigating the example problems.